(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The development of technology used in computerized programs is considered on of the most important topics that is responsible for creating tools that can be used in the business environment, the audit profession is one of those professions that received this development. In order for this profession to be more effective, there must be a tool based on sound (correct) scientific basis that can be based upon to enhance the quality of auditing. The research also aims to propose a computerized program to plan the auditing process according to the methods appropriate to the working environment in the audit offices and companies in Iraq. The computerized program was applied to the research sample and the hypothesis of the research has been proved by a comparison between the planning using the computerized method and the current method used in the same research sample, through this comparison, the research showed that there is (39.35 hours) of work saved by using the computerized method, which in turn enhance the quality of the audit performance by reaching the auditing goal in less time than the approved time, and that in turn achieves performance efficiency as well as implementing all planning paragraphs in record time which enhances efficiency. And through quality, efficiency and reduced working hours, economic development is achieved.